2009
DOI: 10.3171/2009.3.spine08720
|View full text |Cite
|
Sign up to set email alerts
|

Indications for anterior cervical decompression for the treatment of cervical degenerative radiculopathy

Abstract: Object The objective of this systematic review was to use evidence-based medicine to identify the indications and utility of anterior cervical nerve root decompression. Methods The National Library of Medicine and Cochrane Database were queried using MeSH headings and key words relevant to surgical management of cervical radiculopathy. Abstracts were reviewed after which studies meeting inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 24 publications
1
54
1
1
Order By: Relevance
“…First, an updated Cochrane review 51 indicated that surgery for cervical radiculopathy or myelopathy may provide more rapid (ie, short-term) pain relief when compared to physical therapy or hard-collar immobilization, primarily based on low-quality evidence, with virtually no difference in the long-term outcomes. Second, Matz et al 49 indicated similar clinical improvements in certain outcomes when comparing anterior surgical nerve root decompression with or without fusion to physical therapy or cervical immobilization at 12 months. Recently, 2 separate studies 31,54 reported on findings from a randomized clinical trial comparing clinical outcomes in patients who received either ACDF followed by physical therapy or physical therapy alone.…”
Section: T T Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, an updated Cochrane review 51 indicated that surgery for cervical radiculopathy or myelopathy may provide more rapid (ie, short-term) pain relief when compared to physical therapy or hard-collar immobilization, primarily based on low-quality evidence, with virtually no difference in the long-term outcomes. Second, Matz et al 49 indicated similar clinical improvements in certain outcomes when comparing anterior surgical nerve root decompression with or without fusion to physical therapy or cervical immobilization at 12 months. Recently, 2 separate studies 31,54 reported on findings from a randomized clinical trial comparing clinical outcomes in patients who received either ACDF followed by physical therapy or physical therapy alone.…”
Section: T T Discussionmentioning
confidence: 99%
“…13 Moreover, 2-year reoperation rates following ACDF procedures have been reported to range from 6.2% to 14.5%. 1,23,24,28,50 Two recent systematic reviews 49,51 have provided preliminary support for physical therapy as a form of conservative care for individuals presenting with cervical radiculopathy or myelopathy, prior to considering ACDF surgical intervention. First, an updated Cochrane review 51 indicated that surgery for cervical radiculopathy or myelopathy may provide more rapid (ie, short-term) pain relief when compared to physical therapy or hard-collar immobilization, primarily based on low-quality evidence, with virtually no difference in the long-term outcomes.…”
Section: T T Discussionmentioning
confidence: 99%
“…I denne studien fant man ingen sikker forskjell mellom kirurgi og ikke-operativ behandling, men den har vesentlige mangler og deltakerne hadde meget lang symptomvarighet. Gevinsten av kirurgi ser ut til å vaere rask bedring av smertene, langtidseffekten sammenliknet med ikke-operativ behandling er mer usikker (11,13). Et vesentlig spørsmål å stille en pasient med cervikal nerverotsaffeksjon blir derfor om smertene er akseptable i et tidsperspektiv for bedring på 6-12 måne-der.…”
Section: Mistenkt Nerverotsaffeksjonunclassified
“…Patients with persistent CR symptoms and unsatisfactory results after non-surgical treatment may be referred to surgery [7,57,68]. Overall, good effects on arm pain and neurological symptoms have been reported after surgery in patients with CR [3,[9][10][11]75].…”
Section: Rationale Of the Thesismentioning
confidence: 99%
“…Patients with persistent CR symptoms and unsatisfactory results after non-surgical treatment may be referred to surgery [7,57,68]. Surgery primarily aims to address the structural changes in the cervical spine to relieve arm pain and prevent further neurological symptoms by decompressing the nerve root [69].…”
Section: Surgical Treatmentsmentioning
confidence: 99%